PROTOTYPE POWER USE EFFICIENCY SYSTEM ON RFID AND PASSIVE INFRARED ELECTRONIC DEVICES - Siregar , Diana Novita; Lubis, Abdul Jabbar; Lubis, Imran (Pena Cendekia Insani, 2022)
The problem that is often faced today is when we travel out of a room and we forget to turn off electronic devices in the room which results in a surge in costs that must be paid for wasteful use of electronic goods, in this modern era many ways can be done to make automatic system that aims to help human work, in this system the author makes a system that can save electricity usage. By using the PIR sensor to detect movement, and if there is movement inside the room then the electronic goods will live and, if the user wants to use power without having to turn off automatically, then the user can use the RFID card to be affixed to the electronic goods will continue to live until the card is removed from the RFID module, and the buzzer will sound if the user attaches the card to the RFID module incorrectly, to make it easier for the user to see the current conditions, then install the LCD to make it easier for the user to know the current condition.